Use of Palliative Care Services in a Tertiary Cancer Center. (27th November 2015) - Dalal, Shalini; Bruera, Sebastian; Hui, David; Yennu, Sriram; Dev, Rony; Williams, Janet; Masoni, Charles; Ihenacho, Ijeoma; Obasi, Emmanuel; Bruera, Eduardo
Abstract: Background: Despite increasing prevalence of palliative care (PC) services in cancer centers, most referrals to the service occur exceedingly late in the illness trajectory. Over the years, we have made several attempts to promote earlier patient access to our PC program, such as changing the name of our service from PC to supportive care (SC). This study was conducted to determine the use of PC/SC service over the past 8 years. Methods: We reviewed billing data for all PC/SC encounters. We examined five metrics for use: inpatient consultations as a percentage of hospital admissions, ratio of inpatient consultations to average number of operational beds, time from hospital registration to outpatient consultation, time from advanced cancer diagnosis to consultation, and time from first outpatient consultation to death/last follow-up. Results: Over the years, we found a consistent increase in patient referrals to the PC/SC program. In the inpatient setting, we found approximate doubling of the inpatient consultations as a percentage of hospital admissions and the ratio of inpatient consultations to hospital beds (from 10% to 19% and from 2.4 to 4.9, respectively; p < .001). In the outpatient setting, we observed variations in referral pattern between oncology services, but, overall, the time from consultation to death/last follow-up increased from 4.8 months to 7.9 months ( p = .001), which was accompanied by a significant decrease in the interval to consultation from hospital registration and advanced cancer diagnosis ( p < .001). Conclusion: We have observed a consistent annual increase in new patient referrals as well as earlier access for outpatient referrals to our SC service, supporting increased use of palliative care at our cancer center. Abstract : This study analyzed palliative/supportive care use in a single cancer center over 8 years. Billing data showed the inpatient consultations as a percentage of hospital admissions and the ratio of inpatient consultations to hospital beds almost doubled. In the outpatient setting, data revealed earlier access to outpatient referrals to palliative care service (from 4.8 months to 7.9 months; p = .001) during the study period.